Traumatic brain injury in China. Issue 3 (March 2019) - Jiang, Ji-Yao; Gao, Guo-Yi; Feng, Jun-Feng; Mao, Qing; Chen, Li-Gang; Yang, Xiao-Feng; Liu, Jin-Fang; Wang, Yu-Hai; Qiu, Bing-Hui; Huang, Xian-Jian
Summary: China has more patients with traumatic brain injury (TBI) than most other countries in the world, making this condition a major public health concern. Population-based mortality of TBI in China is estimated to be approximately 13 cases per 100 000 people, which is similar to the rates reported in other countries. The implementation of various measures, such as safety legislation for road traffic, establishment of specialised neurosurgical intensive care units, and the development of evidence-based guidelines, have contributed to advancing prevention and care of patients with TBI in China. However, many challenges remain, which are augmented further by regional differences in TBI care. High-level care, such as intracranial pressure monitoring, is not universally available yet. In the past 30 years, the quality of TBI research in China has substantially improved, as evidenced by an increasing number of clinical trials done. The large number of patients with TBI and specialised trauma centres offer unique opportunities for TBI research in China. Furthermore, the formation and development of research collaborations between China and international groups are considered essential to advancing the quality of TBI care and research in China, and to improve quality of life in patients with this condition.